Analyses from a Centre of Short- and Long-Term Growth in Turner’s Syndrome on Standard Growth Hormone Doses Confirm Growth Prediction Algorithms and Show Normal IGF-I Levels - Ranke, Michael B.; Schweizer, Roland; Martin, David D.; Ehehalt, Stefan; Schwarze, Carl-Philipp; Serra, Felice; Binder, Gerhard (Hormone research in paediatrics, 2012)
Aims and Methods: Prediction algorithms suggest factors determining short- and long-term growth response to growth hormone (GH) in Turner’s syndrome (TS). A total of 133 patients (group A; 53% with karyotype 45,X) completed 1 year of treatment and 77 patients (group B) reached adult height (AH) after >4 years on GH treatment. The patients were analysed for factors determining the outcomes, and in addition, the validity of published algorithms was tested. Results: In group A [values are given as medians (10th–90th percentiles)], starting age was 9.4 (4.8–14) years, height was –3.2 (–4.4 to –1.9) SDS (Prader references), and GH dose was 38 (23–48) µg/kg/day. Observed height velocity was 7.7 (5.2–9.8) cm/years and was equal to the predicted height velocity. In group B, projected adult height (PAH) was 147.4 (139.5–154.8) cm. Total gain in height over PAH of 6.1 (2.0–12.6) cm was negatively correlated with height at start, but positively correlated with GH duration, first year Δheight SDS, or index of responsiveness. Observed AH was 153.5 (146.6–160.1) cm and predicted AH was 155.0 (147.4–161.0) cm, which is statistically not different. On GH <5% IGF-I levels were >2 SDS. Conclusions: The published prediction algorithms were found to be valid. If normal AH is to be reached at the lowest costs and risks, probably only TS children with a good growth potential and a high responsiveness to GH can be treated successfully with GH doses of <50 µg/kg/day.